Particular matter influences the incidence of acute otitis media in children - Park, Mina; Han, Jiyeon; Park, Jiwon; Jang, Myoung-jin; Park, Moo Kyun (Scientific reports, 2021)
Particulate matter (PM) is the main component of air pollution. Children are vulnerable to PM and acute otitis media (AOM), which is one of the most common diseases in children. However, studies on the relationship between AOM in children and PM are rare and their results are inconsistent. The aim of this study is to investigate the effect of PM on AOM in children on the basis of the Korea National Health Insurance service (NHIS) claims data. NHIS claim data from 2008 to 2015 was used to identify outpatient visits, antibiotic use to treat AOM, and demographic data. This data was combined with the data on PM 2.5 (≤ 2.5 μm) and PM 10 (≤ 10 μm according to its aerodynamic diameter) level extracted from air pollution data from Korean National Institute of Environmental Research for 16 administrative regions. The children with AOM were divided into three age groups (< 2, 2–4, 5–10 years). Generalized linear Poisson regression model was used to estimate the association between AOM and PM using daily counts of AOM and daily mean PM concentrations. It was adjusted to temperature, wind, humidity, season, year, age, and region. With an increase in PM 2.5 of 10 μg/m 3 , the relative risk of OM increased by 4.5% in children under 2 years of age. The effect of PM 2.5 was strongest influence on the day of exposure. The exposure to PM 10 was related to the incidence of AOM on the day of exposure and the following seven days in all three age groups. The PM concentrations did not strongly affect either AOM duration or the use of antibiotics to cure AOM. The RR in the each lag day after exposure to PM 10 was diverse according to the age groups. Regardless of PM size and children’s age, the PM levels are positively related to the incidence of AOM. Both PM 2.5 and PM 10 have the most adverse effects on children under 2 years of age and on the day of exposure.